Analisis Manajemen Risiko Pembiayaan Murabahah di PT BPRS Artha Madani Kantor Pusat Bekasi - Fawziyah, Zahrina Wardatul; -, Isfandayani (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2019)
Risk management is an important effort that must be made by Islamic Banking to minimize risk.This research is a qualitative research and the methods used are interviews, documentation, andobservation. The research objective was to determine the types of risks in murabahah financing andthe strategy of PT. BPRS Artha Madani in overcoming these risks and to find out the analysis of theimplementation of risk management strategies carried out by PT. BPRS Artha Madani Head OfficeBekasi.Based on the results of the study it is known that the risk management strategy analysis of PT.BPRS Artha Madani using Bank Indonesia Regulation No. 13/23/PBI/2011 and 5 C principles consistof Character, Capacity, Capital, Collateral and Condition of Economy. However, despite implementingthe risk management strategy, banks continue to experience risks, namely in the form of: credit risk(in Islamic banks called as financing risk), operational risk and legal risk due to bank internal factorsin analyzing and external factors from customers.. PT. BPRS Artha Madani in resolving troubledfinancing with intensive billing, reprimand to customers if they do not fulfill their obligations, make arestructuring by rescheduling, reconditioning and restructuring if the financing can still be normalized.However, if there is no hope and the Customer is not able to, then the solution is guaranteed that canbe auctioned through litigation or non-litigation channels.